Co-morbidity and drug treatment in Alzheimer's disease. A cross sectional study of participants in the Dementia Study in Northern Norway - Halvorsen Dag S; Straume Bjørn; Viitanen Matti; Andersen Fred; Engstad Torgeir A (BMC Geriatrics, 2011)
Abstract Background Inappropriate medical treatment of co-morbidities in Alzheimer's disease (AD) is an increasing concern in geriatric medicine. The objective of this study was to compare current drug use related to co-morbidity between individuals with a recent diagnosis of AD and a cognitively healthy control group in a population based clinical trial in Northern Norway. Methods Setting: Nine rural municipalities with 70 000 inhabitants in Northern Norway. Participants: Participants with and without AD recruited in general practice and by population based screening. 187 participants with a recent diagnosis of AD were recruited among community dwellers. Of 791 respondents without cognitive symptoms, 500 were randomly selected and invited to further clinical and cognitive testing. The final control group consisted of 200 cognitively healthy individuals from the same municipalities. Demographic characteristics, data on medical history and current medication were included, and a physical and cognitive examination was performed. The statistical analyses were carried out by independent sample t-test, chi-square, ANCOVA and logistic regression. Results A co-morbidity score was significantly higher in AD participants compared to controls. The mean number of drugs was higher for AD participants compared to controls (5.1 ± 3.6 and 2.9 ± 2.4 respectively, p < 0.001 age and gender adjusted), also when adjusted for co-morbidity. AD participants used significantly more anticholinergic, sedative and antidepressant drugs. For nursing home residents with AD the mean number of drugs was significantly higher compared to AD participants living at home (6.9 ± 3.9 and 4.5 ± 3.3, respectively, p < 0.001). Conclusions AD participants were treated with a significantly higher number of drugs as compared to cognitively healthy controls, even after adjustment for co-morbidity. An inappropriate use of anticholinergic and sedative drugs was identified, especially among nursing home residents with AD. The drug burden and the ...